WORKSHOP TEKNIK BERHITUNG CEPAT DI SEKOLAH DASAR NEGERI (SDN) SASI KEFAMENANU NUSA TENGGARA TIMUR - Zulkaidah Nur Ahzan; Eva Binsasi; Cecilia Novianti Salsinha (LPPM Universitas PGRI Argopuro Jember, 2018)
This dedication motivated by the lack of numeracy ability of most students in Indonesia. So it needs a certain method or technique that can help students in counting quickly and accurately. By providing a method or technique is expected to help students calculate quickly and accurately as well as to empower the maximum brain potential in counting. The purpose of this dedication is to build the basic concepts of students in arithmetic and foster creative ideas through the techniques provided. This workshop was held in SDN Sasi Kefamenanu East Nusa Tenggara within 3 (three) days and involved 4th, 5th, and 6th grade students respectively 15, 15, and 20 student. The First day of Workshop is pre-test and multiplication base 10, second day of workshop is multiplication base 100 and 50. The third day of workshop is multiplication base 20 and post-test. The result of this dedication is that although not of many student are able to solve multiplication with this method but the students have been excited in counting, especially for multiplication operation. For further it is better to do this workshop again for the teacher so that the teachers can do multiplication based on our workshop and forward it to the students.